Tax-Based Marriage Incentives in the Affordable Care Act - Elliott Isaac; Haibin Jiang (Institute of Labor Economics (IZA), 2022)
The Affordable Care Act (ACA) introduced a premium tax credit to help low-income families purchase insurance and an individual mandate penalty to encourage purchasing insurance, but a couple's total tax credit and mandate penalty may differ depending on whether they are married. We use a sample of married and cohabiting couples in the 2012–2017 American Community Surveys and leverage variation in the marriage subsidy created by the ACA's premium tax credit, individual mandate, and Medicaid expansion. Using an instrumental variables approach, we estimate a significant though small positive marriage response that is robust to extensive controls and a placebo sample.
Keywords: J12; I18; H24; 330; marriage; affordable care act; premium tax credit; individual mandate